Expectations of tourism: hope, disappointment and tourism development in Vila Real (Douro, Portugal) - Bordonaro,Lorenzo (2020)
In this article, based on ethnographic research in Vila Real, Portugal, and carried out within the framework of the Dourotur research project, I describe local expectations of tourism in a context of prolonged economic decay and marginalization by national economic policies. Though acknowledging local demands for tourism as legitimate, I question the too straightforward link between tourism and local development that has become a mantra in Portugal. I maintain that, in order to be effective and face local expectations, tourism development policies need to be adapted to local territories and developed in a participative and sustainable form.